2023
DOI: 10.3390/ijms24097703
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 Confers Temozolomide Resistance in Human Glioblastoma Cells and miR-145 Regulates Its Expression

Abstract: Glioblastoma (GBM) is a malignant brain tumor, commonly treated with temozolomide (TMZ). Upregulation of A disintegrin and metalloproteinases (ADAMs) is correlated to malignancy; however, whether ADAMs modulate TMZ sensitivity in GBM cells remains unclear. To explore the role of ADAMs in TMZ resistance, we analyzed changes in ADAM expression following TMZ treatment using RNA sequencing and noted that ADAM17 was markedly upregulated. Hence, we established TMZ-resistant cell lines to elucidate the role of ADAM17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…2D ). During stressful conditions such as starvation or chemotherapy, cancer cells may activate certain signaling pathways that give them an advantage in survival ( 37 ). Therefore, U87MG and U87MGR cells were cultured in serum-free medium for 24 and 48 h and the changes in HGF expression and MET activation upon starvation were assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D ). During stressful conditions such as starvation or chemotherapy, cancer cells may activate certain signaling pathways that give them an advantage in survival ( 37 ). Therefore, U87MG and U87MGR cells were cultured in serum-free medium for 24 and 48 h and the changes in HGF expression and MET activation upon starvation were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the present findings, another GBM cell line, DBTRG-05MG cells, were selected to investigate the effect of lidocaine on the MET pathway and further analyze its relationship with TMZ sensitivity and cell migration. This choice was based on a previous study by the authors, which revealed that DBTRG-05MG cells exhibit a high level of resistance to TMZ ( 37 ). The DBTRG-05MG cells were cultured in a serum-free medium for 24 and 48 h, and the impact of starvation on MET activation was evaluated using western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ADAM17 is responsible for pathological and physiological processes, such as cell growth, inflammation, differentiation, regeneration, and tumor progression [ 97 ]. It was identified that miR-145-5p increased TMZ sensitivity in GBM cells by ADAM17 targeting [ 99 ].…”
Section: Wnt/β-catenin and Pi3k/akt Signaling Pathwaysmentioning
confidence: 99%
“…In recent years, many studies focused on the regulatory role of miRNAs as the core of the competitive endogenous RNA (ceRNA) hypothesis that explains the relationship between different classes of RNAs including circRNA, long noncoding RNA (lncRNA), miRNAs and mRNAs 9 . Hsa-miR-145-5p , one of the targets of several dysregulated circRNAs identified in studies, has been widely confirmed to be associated with cancer 8 , 10 . Evidence has shown that miR-145-5p can be regulated by different mechanisms and can involve in tumorigenesis and progression through binding to 3′-UTRs of target mRNAs 10 , 11 .…”
Section: Introductionmentioning
confidence: 98%
“…Hsa-miR-145-5p , one of the targets of several dysregulated circRNAs identified in studies, has been widely confirmed to be associated with cancer 8 , 10 . Evidence has shown that miR-145-5p can be regulated by different mechanisms and can involve in tumorigenesis and progression through binding to 3′-UTRs of target mRNAs 10 , 11 . Several studies have reported that miR-145-5p can significantly suppress tumor progression, including in colorectal cancer (CRC) 12 , lung cancer 13 , and glioma 14 via targeting epidermal growth factor receptor (EGFR) gene.…”
Section: Introductionmentioning
confidence: 98%